P8 Visual hallucinations in a patient treated with ACE inhibitors. Issue 10 (7th September 2012) - Corretge, M; Ramsay, S; Aditya, H
Abstract : Objective: To present a case in which ACE inhibitors were found to be the cause for a patient's visual hallucinations and to explore the different reasons that led to this adverse effect. Method: Case report and literature review. Results: Our patient developed visual hallucinations in the absence of other features of delirium, soon after her ACE inhibitor therapy had been increased. She had a background of ischaemic and haemorrhagic stroke. Her symptom disappeared when the ACE inhibitor was stopped. There have been two case reports of visual hallucinations caused by ACE inhibitors published, and also reports in pharmacovigilance documents, however this side effect is not recognised in the British National Formulary. Three different physiological pathways have been suggested as possible causes for the neuropsychiatric symptoms (visual hallucinations and others, such as severe depression and enhancement of cognition) in the case of ACE inhibitors: A protease action over the enzyme encephalinase, an action over the Corticotrophin Releasing Factor leading to the increase of cortisol and finally, through the direct effect of the suppression of the ACE enzyme in the brain, that can affect circulating levels of Acetylcholine. Conclusion: ACE inhibitors have central actions that can account for a variety of neurocognitive symptoms, including visual hallucinations. Stopping therapy can sometimes result in the resolution of these symptoms. Clinicians should be aware of this rare but serious adverse effect associated with this commonly used drug.